Mechanical properties of RCC column with kevlar and banana fibre wrapping. (2021) - Prakhash, N.; Sakthivel, P.; Dhivakar Karthick, M.; Swaminathan, P.; Zunaithur Rahman, D.
Abstract: The development of high-performance materials made from fibers increasing worldwide in recent years. Fibers offer both cost savings as well as an extension of the life span of the building when compared to other conventional materials. However, the strength of building can improve using fibers. The following preliminary research investigated the use of Kevlar, Banana Fabric fiber as possible to improve the impact properties. The main reason for choosing these fibers has high mechanical resistance such as tensile strength and comparative compressive strength addition to that high thermal resistance, corrosion resistance. The concept should be highly implemented in repair and rehabilitation work and environmentally affected zone. This application is necessary for earthquake resistance building, aquatic structures. Kevlar is about five times lighter than steel in terms of the same tensile strength. It is the strongest textile fiber available today. This investigation aims to increase the mechanical properties of the RCC column. Fiber is improved and finds its application in a higher position while comparing to the conventional materials.